Analyzing Divergent Thinking Ability of Students on The Topic of Linear Equations in Grade VIII of State Junior High School (International Journal of Environmental Sciences, 2025)
Divergent thinking is a type of creative thinking that can provide various possible answers based on the information provided. A person with a divergent thinking type generally likes to experiment or try new things. The purpose of this study was to analyze the divergent thinking skills of class VIII students of SMP Negeri 1 Dampit on the material of linear equations. This study is a qualitative study with a descriptive research design. The instruments used were divergent thinking ability tests and interviews. The indicators of divergent thinking ability are fluency, flexibility, originality, and elaboration. The results of this study are: (1) for the fluency indicator, students gave wrong answers but the mathematical procedure was appropriate, because students were in a hurry when working; (2) for the flexibility indicator, students were not able to find more than one way to solve the problem; (3) for the originality indicator, students solved the problem differently and according to the concept; and (4) for the elaboration indicator, students described the solution in detail and according to the concept but the answer was not correct.